Report of Incidence and Mortality in China Cancer Registries, 2008 - Chen, Wan-qing; Zheng, Rong-shou; Zhang, Si-wei; Li, Ni; Zhao, Ping; Li, Guang-lin; Wu, Liang-you; He, Jie (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: Annual cancer incidence and mortality in 2008 were provided by National Central Cancer Registry in China, which data were collected from population-based cancer registries in 2011. Methods: There were 56 registries submitted their data in 2008. After checking and evaluating the data quality, total 41 registries’ data were accepted and pooled for analysis. Incidence and mortality rates by area (urban or rural areas) were assessed, as well as the age- and sex-specific rates, age-standardized rates, proportions and cumulative rate. Results: The coverage population of the 41 registries was 66,138,784 with 52,158,495 in urban areas and 13,980,289 in rural areas. There were 197,833 new cancer cases and 122,136 deaths in cancer with mortality to incidence ratio of 0.62. The morphological verified rate was 69.33%, and 2.23% of cases were identified by death certificate only. The crude cancer incidence rate in all areas was 299.12/100,000 (330.16/100,000 in male and 267.56/100,000 in female) and the age-standardized incidence rates by Chinese standard population (ASIRC) and world standard population (ASIRW) were 148.75/100,000 and 194.99/100,000, respectively. The cumulative incidence rate (0–74 years old) was of 22.27%. The crude incidence rate in urban areas was higher than that in rural areas. However, after adjusted by age, the incidence rate in urban was lower than that in rural. The crude cancer mortality was 184.67/100,000 (228.14/100,000 in male and 140.48/100,000 in female), and the age-standardized mortality rates by Chinese standard population (ASMRC) and by world population were 84.36/100,000 and 114.32/100,000, respectively. The cumulative mortality rate (0–74 years old) was of 12.89%. Age-adjusted mortality rates in urban areas were lower than that in rural areas. The most common cancer sites were lung, stomach, colon-rectum, liver, esophagus, pancreas, brain, lymphoma, breast and cervix which accounted for 75% of all cancer incidence. Lung cancer was the leading cause of cancer death, followed by gastric cancer, liver cancer, esophageal cancer, colorectal cancer and pancreas cancer, which accounted for 80% of all cancer deaths. The cancer spectrum varied by areas and sex in rural areas, cancers from digestive system were more common, such as esophageal cancer, gastric cancer and liver cancer, while incidence rates of lung cancer and colorectal cancer were much higher in urban areas. In addition, breast cancer was the most common cancer in urban women followed by liver cancer, gastric cancer and colorectal cancer. Conclusion: Lung cancer, gastric cancer, colorectal cancer, liver cancer, esophageal cancer and female breast cancer contributed to the increased incidence of cancer, which should be paid more attention to in further national cancer prevention and control program. Different cancer control strategies should be carried out due to the varied cancer spectrum in different groups.